Novel spirofluorene/indole/carbazole-based hole transport materials with high triplet energy for efficient green phosphorescent organic light-emitting diodes. (February 2017) - Dong, Qingchen; Lian, Hong; Gao, Zhixiang; Guo, Zeling; Xiang, Ning; Zhong, Zheng; Guo, Hongen; Huang, Jinhai; Wong, Wai-Yeung
Abstract: Three novel host materials 9-(4-(5-(4-(9-phenyl-9H-fluoren-9-yl)phenyl)-1H-indol-1-yl)phenyl)-9H-carbazole (C1 ), 9-(4-(9, 9-diphenyl-9H-fluoren-4-yl)-1H-indol-1-yl)-9-phenyl-9H-carbazole (C2 ) and 9-(4-(5-(9, 9-diphenyl-9H-fluoren-2-yl)-1H-indol-1-yl)phenyl)-9H-carbazole (C3 ) based on spirofluorene, indole and carbazole derivatives have been designed and synthesized. Their thermal, photophysical and electrochemical properties were fully investigated. The OLED devices withC1 –C3 as host were fabricated to investigate their electroluminescent properties. CompoundC3 obtained the best device performances with the maximum current efficiency of 45.2 cd A −1 and the maximum power efficiency of 23.2 lm W −1 for green phosphorescent organic light-emitting diodes. Graphical abstract: Highlights: Three novel host materials based on spirofluorene/indole/carbazole derivatives were developed. CompoundC3 exhibits a high glass transition temperature of 165 °C and high triplet energy level of 3.204 eV. Green PhOLED withC3 as host exhibits the best performance (ηc, max = 45.2 cd/A and ηp, max = 23.2 lm/W).